Modelo de pagamento por performance na remuneração médica em uma cooperativa de saúde no sul do brasil - Talevi, Fabiana Pastro (2018)
Due to the complexity of health experienced in the world scenario, it is necessary to reorganize and implement new health models aimed at better utilization of financial resources, thus linking quality to the provision of services. aced with the problem of the growing cost of the health system, due in particular to the increase in the implementation of often unnecessary procedures, the increase in the complexity of technologies, medical dissatisfaction due to low remuneration and restriction of access to health care, due to the low salary, changes and the improvement of the remuneration models to the providers are necessary (BESSA, 2011). Performance Payment (P4P) is a pay model that aims to reward providers for the adequacy of patient care and the high quality provided by the supplementary health systems. The objective of the study was to hypothetically evaluate the viability of P4P implantation versus the costs of a labor cooperative in the south of Paraná in the years of 2015 and 2016, verifying if such implementation would reduce costs. The hypothesis discusses the feasibility of adjusting cost and quality of service due to the implementation of the payment model to providers. This research has a quantitative and retrospective approach, using information from the years 2015 and 2016. Variables characterizing the activities of 10 medical specialties (indicators) were collected, as well as the cost effective for them. The performance index for each specialty chosen was calculated using the indicators of the effectiveness and efficiency domains of the P4P model. After obtaining this index, the hypothetical cost to be paid to the providers of each specialty was calculated, which was compared to the actual cost effected to them. For this comparison the repeated measures ANOVA test was applied, followed by the Fisher’s LCD test (p=0.05). In this study it was verified that there was an increase in the cost effected over the two years evaluated, occurring due to the increase in the number of clients, the use of new technologies, and also the increase due to inflation. If P4P were implemented, cost savings were estimated at approximately 6% in 2015 and 9% in 2016.